The arrival of offshore wind farms on the coast of Rio Grande do Norte and potential socio-environmental conflicts - Freire, Eugenia França; Nunes, Maria Fernanda Santos Quintela da Costa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2025)
Offshore wind generation has aroused the interest of various sectors and entities in Brazil, mainly because of its high capacity to generate energy within the energy transition scenario. After IBAMA issued the Terms of Reference for the Environmental Impact Study, the number of registered projects increased significantly. Although there are no offshore wind farms installed in Brazil, onshore generation stands out, especially in the state of Rio Grande do Norte, whose region is characterized by high wind speeds. Despite the increase in energy generation associated with offshore wind farms, the arrival of new developments could trigger socio-environmental conflicts in the marine space already occupied by various activities. The main conflicts identified are dealt with in this paper, namely: limitation of areas for artisanal fishing, alteration of the natural landscape, damage to tourist and sporting activities, limitations on maritime travel and risks to biodiversity. The analysis of these potential conflicts indicates the need to implement Marine Spatial Planning (MSP) and increase investment in biodiversity studies in order to analyze the main environmental impacts of offshore wind farms within the Brazilian context.